Microbial Metabolic Genes Crucial for S. aureus Biofilms: An Insight From Re-analysis of Publicly Available Microarray Datasets - Nassar, Rania; Hachim, Mahmood; Nassar, Mohannad; Kaklamanos, Eleftherios G.; Jamal, Mohamed; Williams, David; Senok, Abiola (Frontiers in Microbiology, 2021)
Bacterial biofilms are microbial lifestyles found in all environments. Up to 80% of human infections and 60–70% of hospital-acquired infections have a biofilm origin, with Staphylococcus aureus one of the leading causes of these infections. Microorganisms in biofilms exhibit significant antimicrobial resistance which poses important treatment challenges, hence the urgent need to identify novel antibiofilm strategies. Microbes form biofilms in response to various factors, and once these 3-dimentional structures form they are highly recalcitrant to removal. The switch from planktonic lifestyle to the biofilm protected mode of growth results in a phenotypic shift in the behavior of the microorganisms in terms of growth rate and gene expression. Given these changes, investigation of microbial gene expression and their modulation at different stages of biofilm maturation is needed to provide vital insight into the behavior of biofilm cells. In this study, we analyzed publicly available transcriptomic dataset of S. aureus biofilms at different stages of maturation to identify consistently upregulated genes irrespective of the biofilm maturation stage. Our reanalysis identified a total of 6 differentially expressed genes upregulated in both 48 and 144-h old S. aureus biofilms. Functional analysis revealed that these genes encode for proteins which play a role in key microbial metabolic pathways. However, these genes, as yet, are unrelated or fully studied in the context of biofilm. Moreover, the findings of this in silico work, suggest that these genes may represent potential novel targets for the development of more effective antibiofilm strategies against S. aureus biofilm-associated infections.